Wilhelm Meisters Lehrjahre $1 (BBand 5s - Goethe, Johann Wolfgang von, 1749-1832 (Salt Lake City, UT : Project Gutenberg, 2000)
"Wilhelm Meisters Lehrjahre $1 (BBand 5" by Johann Wolfgang von Goethe is a novel written during the late 18th century. This part of Goethe's larger work delves into the journey of Wilhelm as he navigates personal and professional challenges, particularly surrounding his aspirations in the theater and complex relationships with those around him. The opening of this volume introduces us to Wilhelm, who is dealing with emotional turmoil following the death of his father. He is also confronted with the complexities of his relationships, particularly with Aurelie, Felix, and a young girl named Mignon. As Wilhelm grapples with his circumstances, his companions react to his situation in varied ways; Mignon, for example, finds solace in learning and caring for Felix, while Wilhelm contemplates his path towards becoming a theatrical actor, influenced by the expectations and dynamics within the theater. The narrative poignantly illustrates themes of love, ambition, and the challenges of self-discovery. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Wilhelm_Meister%27s_Apprenticeship
Release date is 2000-09-01
This etext was prepared by Michael Pullen
Keywords: Bildungsromans; Theater, Traveling -- Fiction